2011
DOI: 10.1111/j.1365-2753.2011.01765.x
|View full text |Cite
|
Sign up to set email alerts
|

How doctors practice evidence‐based medicine

Abstract: Our study suggested that EBM was still not well practised, using rosiglitazone prescription as a study case. Further education and encouragement to strengthen physicians' EBM practice remain urgently needed within the medical community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Moreover, healthcare workers in Saudi Arabia have a good culture of incorporating evidencebased practice in the management of patients. [17] It is, therefore, evident that diabetic patients in Saudi Arabia benefit from doctors who are updated with the latest information on the management of diabetes. [18,19] Posts that wellinformed patients positively influence the quality of health services rendered to them.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, healthcare workers in Saudi Arabia have a good culture of incorporating evidencebased practice in the management of patients. [17] It is, therefore, evident that diabetic patients in Saudi Arabia benefit from doctors who are updated with the latest information on the management of diabetes. [18,19] Posts that wellinformed patients positively influence the quality of health services rendered to them.…”
Section: Discussionmentioning
confidence: 99%
“…The vital role that the development of clinical research plays in the effectiveness of evidence-based Copyright: © 2020 PPCR. The Principles and Practice of Clinical Research medicine has been shown by many authors (Lu & Li, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Improvements in clinical research methods have effected widespread support of evidence-based medicine. 1 , 2 Although evidence-based medicine aims to improve clinical care, it challenges clinicians and researchers. 3 , 4 Moderate-to-advanced knowledge of the methodology is necessary to apply the resulting findings into practice and assess the cost-effectiveness of new interventions.…”
Section: Introductionmentioning
confidence: 99%